(untitled) (Research, Society and Development, 2020)
Introduction: Drug trafficking is an important factor in the increase of homicide, since it has to fight for territory to carry out its market, which recruits young people, mostly blacks, poor and residents of the periphery, as cheap labor. Objectives: To highlight the geography of homicides and to seek to verify the spatial correlation existing between the occurrence of homicide and drug trafficking. Methods: For spatial analysis, we selected the four-year Bayesian rate of homicide against adolescent and drug trafficking to evaluate the spatial correlation between these two phenomena. Results: The results show that there is a spatial relation to homicide rates against adolescent and drug trafficking. Conclusion: There is a spatial pattern of the distribution of homicide against adolescents and drug trafficking in the municipality of Belém, which shows that drug trafficking is a contributing factor to the increase in homicide in the territory.